2022
DOI: 10.1371/journal.pone.0261559
|View full text |Cite
|
Sign up to set email alerts
|

Conspiracy beliefs and vaccination intent for COVID-19 in an infodemic

Abstract: Background The massive, free and unrestricted exchange of information on the social media during the Covid-19 pandemic has set fertile grounds for fear, uncertainty and the rise of fake news related to the virus. This “viral” spread of fake news created an “infodemic” that threatened the compliance with public health guidelines and recommendations. Objective This study aims to describe the trust in social media platforms and the exposure to fake news about COVID-19 in Lebanon and to explore their association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 48 publications
6
41
0
6
Order By: Relevance
“…Availability and accessibility to information on COVID-19 vaccination are crucial for the general population to help the individuals to make informed decisions and to have safe preventive behaviors. The positive effect of the information received from institutional and scientific sources on the correct perception of the severity of COVID-19 aligns well with the results from previous research which found that the exposure to these sources have a positive impact on the level of knowledge, on the attitudes, and on the acceptability of the vaccination than those exposed to other sources [ 12 , 17 , 18 , 19 , 20 , 21 ]. Moreover, it was particularly notable that the internet has become the third major source for respondents seeking vaccine information.…”
Section: Discussionsupporting
confidence: 88%
“…Availability and accessibility to information on COVID-19 vaccination are crucial for the general population to help the individuals to make informed decisions and to have safe preventive behaviors. The positive effect of the information received from institutional and scientific sources on the correct perception of the severity of COVID-19 aligns well with the results from previous research which found that the exposure to these sources have a positive impact on the level of knowledge, on the attitudes, and on the acceptability of the vaccination than those exposed to other sources [ 12 , 17 , 18 , 19 , 20 , 21 ]. Moreover, it was particularly notable that the internet has become the third major source for respondents seeking vaccine information.…”
Section: Discussionsupporting
confidence: 88%
“…This is a very critical concern because urban dwellers are largely educated with a significant presence on several social media platforms [ 41 ]. In some previous studies, several authors have reported negative association between social media exposure and the acceptance of COVID-19 vaccines [ 66 , 67 , 68 , 69 , 70 , 71 , 72 ], while others reported positive association [ 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most researchers note that the enormous surge of conspiracy ideas may be well explained by unprecedented levels of globalisation [ 16 , 17 ], digitisation [ 17 ], cultural unification [ 18 ], diminished levels of information quality/controllability in pandemic times [ 19 ], “bloggification” (the emergence of an almost endless amount of sources of information and centres of ideological influence on the Internet: personal blogs, independent media, independent health care experts, etc.) [ 20 ], and distrust towards the public policy [ 21 ]. Social media has been a useful vehicle for the instantaneous spread of conspiracy ideas about COVID-19 vaccination across huge audiences, a phenomenon that was not a feature of former epidemics, pandemics, or health care crises.…”
Section: Covid-19-related Conspiracy Theories As a Factor Of Vaccine ...mentioning
confidence: 99%